Principles for determining effective parameters for organizing train traffic in suburban-urban traffic, taking into account the differentiation of service classes - A. F. Borodin; I. F. Mustafin; K. Yu. Nikolaev (Вестник Научно-исследовательского института железнодорожного транспорта, 2021)
Introduction of a new transport product in urban agglomerations helps to attract additional passenger traffic by changing parameters of organizing the operation of suburban trains. Problem of determining the effective parameters of the route network of suburban-urban railway communication in order to achieve acceptable financial results for the owners of infrastructure and carriers is considered. Controlled variables are determined that characterize the route network of suburban-urban traffic and include the type of train schedule, the operation interval, the routes, the traffic volume of suburban-urban trains, the station of departure and arrival, the service class. It was also determined that the distribution of passenger traffic correspondence over the network of transport products depends both on a set of controllable variables and on the time of travel by rail when using a transport product, taking into account the execution of terminal operations at points of departure, destination, transfers, waiting for trains, and travel on trains. The objective function for the carrier and the owner of the infrastructure, which is identical for both participants of transportation, is considered, while the components of investment costs and direct production costs for transportation activities and income receipts that ensure the break-even of this activity are different for each participant in transport services. Relevant constraints for the task, due to the resources of the railway infrastructure and rolling stock, have been determined. Authors provides the principles of solving this multicriteria problem by finding a group of the best options by a directed enumeration of alternatives with the subsequent selection of the resulting solution by the methods of compromise control. The research results are intended for use in projects for the development of suburban-urban traffic in large urban agglomerations.